2016
DOI: 10.13005/bbra/2068
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adenosine Deaminase: A Novel Biomarker Tool for the Diagnosis of Tuberculosis

Abstract: Tuberculosis is a major health issues worldwide. Every year more than 9 million new cases are reported worldwide with death rate of around 2 million each year. Rapid and accurate diagnosis of tuberculosis in population is most supportive in proper medication and early recovery. The golden standard method for diagnosis of tuberculosis in patient is formerly culture method which is time consuming and cumbersome. Various other techniques used in the diagnosis of tuberculosis have poor sensitivity and specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Kynurenine is known to correlate with increased expression of indoleamine 2,3-dioxygenase upon contact with M. tuberculosis, while adenosine deaminase, which enzymatically converts adenosine to inosine, has been identified as a potential serum proteomic biomarker for TB. 40 [ 2 9 _ T D $ D I F F ] Zhou et al confirmed some of these findings in a nuclear magnetic resonance (NMR) rather than mass spectrometry based approach. 41 [ 3 0 _ T D $ D I F F ] Another study also showed changes in metabolic profiles upon TB drug treatment; however, the study design did not allow for an unambiguous annotation of the unique molecular features collected.…”
Section: [ 2 2 _ T D $ D I F F ]mentioning
confidence: 98%
“…Kynurenine is known to correlate with increased expression of indoleamine 2,3-dioxygenase upon contact with M. tuberculosis, while adenosine deaminase, which enzymatically converts adenosine to inosine, has been identified as a potential serum proteomic biomarker for TB. 40 [ 2 9 _ T D $ D I F F ] Zhou et al confirmed some of these findings in a nuclear magnetic resonance (NMR) rather than mass spectrometry based approach. 41 [ 3 0 _ T D $ D I F F ] Another study also showed changes in metabolic profiles upon TB drug treatment; however, the study design did not allow for an unambiguous annotation of the unique molecular features collected.…”
Section: [ 2 2 _ T D $ D I F F ]mentioning
confidence: 98%
“…Previously, the culture technique was the gold standard for diagnosing TB patients, although it is time-consuming and labor-intensive and other techniques for diagnosing TB possess low sensitivity and specificity ( Pandey et al., 2016 ). Furthermore, the aforementioned mycobacterial species discovered several strategies to build a viable human habitat, including modulating host immunological response.…”
Section: Multi-omics Approaches To Study Mycobacterial Diseasesmentioning
confidence: 99%
“…This proteomic approach is utilized to identify appropriate host biomarkers in mycobacterial disease ( De Groote et al., 2013 ). Another research found that serum adenosine deaminase enzymatically converts adenosine to inosine as a possible serum proteomic biomarker for TB that may be utilized to quickly and efficiently diagnose TB ( Pandey et al., 2016 ). Proteome microarray research allowed screening of blood serum from individuals with active TB and latent TB infection and found that RV2031c, RV2421c,and RV1408 were possible serum biomarkers for distinguishing active TB from latent TB infection ( Cao et al., 2018 ).…”
Section: Multi-omics Approaches To Study Mycobacterial Diseasesmentioning
confidence: 99%
“…ADA seems to be an index for cellular immunity. [5] Nowadays measurement of ADA levels is the gold standard for the diagnosis of tuberculous pleural effusion in developing countries. [6] More recently, WHO endorsed the GeneXpert(1) for the diagnosis of TB.…”
Section: Introductionmentioning
confidence: 99%